Mechanical Characteristics of Concrete with Addition of Nickel Slag Waste as Aggregates - Pelupessy, Safriyati; Mufrodi, Zahrul; Suharto, Totok Eka (Indonesian Journal of Chemical Engineering, 2024)
Ferronickel slag is a waste product of the nickel metal smelting industry. PT. Virtue Dragon Nickel Industry is a company located in Konawe, Southeast Sulawesi Province, which is the first ferronickel and stainless-steel industrial area in Indonesia. Since 2017 until now, the capacity of the ferronickel smelting industry in the company is 600,000 tons. From the ferronickel smelting process, slag waste of around 3 million tons has also been produced which has not been processed or utilized. Slag waste is feared to disrupt the environment if not managed or utilized properly. This study aims to study the utilization of nickel slag waste as a substitute for fine and coarse aggregate in concrete. This study compares the mechanical properties of concrete using nickel slag material with the use of natural materials in the form of gravel and sand taken from the Konaweha River. The study was started with the preparation of nickel slag in the size of coarse aggregate 10-20 mm, and fine aggregate that passes 20 mesh. Nickel slag was tested for its content or composition. Slag was mixed into a concrete mixture containing sand, gravel, cement with a certain composition. The slag content was added at 0, 10, 20 and 30%. The stirred mixture was then tested for slump with an Abrams cylinder with a lower diameter of 20 cm, an upper diameter of 10 cm and a height of 30 cm. The mixture was molded in the form of a cube measuring 15 cm x 15 cm x 15 cm for density testing and compressive strength testing after 28 days. The test results showed that the largest slag content was silica and iron. The addition of nickel slag provided a slump value that was still included in the type of mixture with good performance. The addition of nickel slag up to 30% increased the density and compressive strength of concrete. The density of concrete increased by 6.7-21.9%. The increase in concrete compressive strength ranges from 8.43 to 33.79%. The mixture with the addition of 20% fine slag has the highest compressive strength of 33.23 MPa.